2016
DOI: 10.30750/ijpbr.4.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Beekeeping and Bee Products; Boon for Human Health and Wealth

Abstract: The cross-fertilization by bee increases average agricultural yield by 20 to 25 percent. Its products like honey, pollen, royal jelly, propolis, bee venom have immense medical importance. Honey is useful for healing the wounds, helps to build up hemoglobin, used as laxative blood purifier, preventive against cold, cough, sore throat, eye ailments, burns and gastrointestinal disorder etc. Honey has antibiotic property and is effective in reducing the risk of heart disease, cancer and diabetes. Pollen lowers blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…About one third of the participants believe that T&CM may help them in their business life. Considering that such applications as phytotherapy and musicotherapy can be used for students in order to boost academic success (20)(21), it can be hypothesised that business success can be boosted by utilising ozone therapy for muscle pains and apitherapy for lack of energy (22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…About one third of the participants believe that T&CM may help them in their business life. Considering that such applications as phytotherapy and musicotherapy can be used for students in order to boost academic success (20)(21), it can be hypothesised that business success can be boosted by utilising ozone therapy for muscle pains and apitherapy for lack of energy (22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Honey is composed of “sugars” ( Kamal and Klein, 2011 ), “disaccharides,” “water,” “proteins” ( Moreira et al, 2007 ; Won et al, 2009 ; Sak-Bosnar and Sakač, 2012 ), “amino acids” ( Hermosí;n et al, 2003 ; Iglesias et al, 2006 ), “vitamins” ( Bonté and Desmoulière, 2013 ), “minerals” ( Alqarni et al, 2014 ), “organic acids,” “phenolic compounds” ( Andersen and Markham, 2005 ), and “solid particles” ( Castro-Vázquez et al, 2007 ) as well as “volatile compounds” ( Da Silva et al, 2016 ). Honey is used as a remedy in traditional medicine to cure gastritis, snake-bite, cold, myalgia, eye infection, teething in child, dark spots, skin, diarrhea, expectorant, migraine, allergy, burns, wounds in the stomach, spleen, toothache, mouth, influenza, hypertension, atherosclerosis, diabetes mellitus, Alzheimer’s disease, cancer, urinary system, throat pain, asthma, acidity obesity, cough, and tonsils ( Mahawar and Jaroli, 2006 ; Padmanabhan and Sujana, 2008 ; Dixit et al, 2010 ; Jaroli et al, 2010 ; Oliveira et al, 2010 ; Abbasi et al, 2011 ; Benítez, 2011 ; Deb and Haque, 2011 ; Lohani, 2011b ; Yirga et al, 2011 ; Barros et al, 2012 ; Erejuwa et al, 2012 ; Haileselasie, 2012 ; Chinlampianga et al, 2013 ; Betlloch Mas et al, 201 7; Mootoosamy and Mahomoodally, 2014 ; Sreekeesoon and Mahomoodally, 2014 ; Vallejo and González, 2014 ; Vijayakumar et al, 2015b ; Waykar and Alqadhi, 2016 ; Yeshi et al, 2017 ; Altaf et al, 2018 ; Altaf and Umair, 2020 ). Honey is also utilized in nano-medicine to cure various ailments and acts as anti-apoptosis, anti-proliferative ( Oršolić, 2009 ; Li et al, 2010 ; Mandal and Mandal, 2011 ; Vallianou et al, 2014 ), anti-diabetic, antioxidant ( Omotayo et al, 2010 ; Erejuwa, 2014 ; Bobiş et al, 2018 ), antibiotic, anti-cataract, anti-inflammatory, antifungal and endophthalmitis ( Rhone and Basu, 2008 ; Vit and Jacob, 2008 ; Cernak et al, 2012 ; Salehi et al, 2014 ...…”
Section: Discussionmentioning
confidence: 99%
“…Honey has antimicrobial, antioxidant and anti-inflammatory properties. Research study reported that in temperate climates and places with considerable temperature fluctuations, honey is a well-known remedy for colds and mouth, throat or bronchial irritations and infections (19). There is increasing evidence that a single dose of honey might reduce mucus secretion and reduce cough in children.…”
Section: Discussionmentioning
confidence: 99%